Winter to spring transition and diurnal variation of VOCs in Finland at an urban background site and a rural site - Patokoski, Johanna; Ruuskanen, Taina M.; Hellen, Heidi; Taipale, Risto; Gronholm, Tiia; Kajos, Maija K.; Petaja, Tuukka; Hakola, Hannele; Kulmala, Markku; Rinne, Janne (Finnish Environment Institute, 2016)
Peer reviewed